Intrinsic Mitochondrial Reactive Oxygen Species (ROS) Activate the In Situ Synthesis of Trimethine Cyanines in Cancer Cells. Issue 38 (8th August 2022) - Heng, Hao; Song, Gang; Cai, Xuetong; Sun, Jian; Du, Ke; Zhang, Xiaoran; Wang, Xia; Feng, Fude; Wang, Shu
Abstract: Environment‐responsive in situ synthesis of molecular fluorescent dyes is challenging. Herein, we develop a photoextension strategy to make trimethine cyanines with decent conversion efficiency (up to 81 %) using 1‐butyl 2, 3, 3‐trimethyl 3 H ‐indole derivatives as the sole precursors, and demonstrate a free radical mechanism. In the inducer‐extension stage, free radicals and reactive oxygen species (ROS) were able to mediate similar reactions with no assistance of light. We explored a Mito‐extension strategy to in situ synthesize trimethine cyanines in the living cells. The cellular ROS‐dependence provided a foundation for preferential cyanine expression in cancer cells. Finally, we applied an iodized precursor as an intrinsic ROS‐activated theranostic agent that integrated mitochondria‐targeted cyanine synthesis, cell imaging and phototherapy. Abstract : Trimethine cyanines are synthesized from precursors, assisted by visible light, free radicals or reactive oxygen species (ROS). The reaction can proceed in situ in live cells. The correlation of cyanine expression with the intrinsic cellular ROS production level causes more efficient cyanine production in the cancer cells. The study bridges ROS‐activated in‐cell synthetic chemistry and cancer theranostics.